Blended Learning in Physiotherapy Education: Magic Mix That Improves Quality of Student Learning - Balaraman, Thirumalaya; Swaminathan, Narasimman; Sliwinski, Zbigniew; Kiljanski, Marek (2016)
Background. Teaching face to face and partly online is called blended teaching. In practical oriented subjects like physiotherapy more hands on training is required. Hence online teaching may not help to meet the learning outcomes. But a combination of face to face and online may be very effective in delivering the course contents. In this paper the effect of blended teaching on students learning is discussed. Aim. The aim of this paper is to discuss the efficacy of blended learning to improve the quality of student learning in physiotherapy education. Materials and methods. At INTI International University, we delivered physiotherapy selected courses in blended mode using various tools in the Blackboard platform. We also used zoom and skype to deliver in-classroom lectures with international expert from overseas. The efficacy of this method was evaluated through student’s feedback and performance in the formative and summative assessments Results. The students participated in these courses perceived blended teaching strategies very effective and convenient. Blended learning encouraged more collaboration between students which was evident based on their summative exam scores. Conclusion. Blended teaching strategies may be effective in physiotherapy education to improve the quality of students learning. A higher quality studies will provide more evidence.